Holocene and Pleistocene fringing reef growth and the role of accommodation space and exposure to waves and currents (Bora Bora, Society Islands, French Polynesia). Issue 1 (31st October 2018) - Gischler, Eberhard; Hudson, J. Harold; Humblet, Marc; Braga, Juan Carlos; Schmitt, Dominik; Isaack, Anja; Eisenhauer, Anton; Camoin, Gilbert F.
Abstract: Holocene fringing reef development around Bora Bora is controlled by variations in accommodation space (as a function of sea‐level and antecedent topography) and exposure to waves and currents. Subsidence ranged from 0 to 0·11 m kyr −1, and did not create significant accommodation space. A windward fringing reef started to grow 8·7 kyr bp, retrograded towards the coast over a Pleistocene fringing reef until ca 6·0 kyr bp, and then prograded towards the lagoon after sea‐level had reached its present level. The retrograding portion of the reef is dominated by corals, calcareous algae and microbialite frameworks; the prograding portion is largely detrital. The reef is up to 13·5 m thick and accreted vertically with an average rate of 3·12 m kyr −1 . Lateral growth amounts to 13·3 m kyr −1 . Reef corals are dominated by an inner Pocillopora assemblage and an outer Acropora assemblage. Both assemblages comprise thick crusts of coralline algae. Palaeobathymetry suggests deposition in 0 to 10 m depth. An underlying Pleistocene fringing reef formed during the sea‐level highstand of Marine Isotope Stage 5e, and is also characterized by the occurrence of corals, coralline algal crusts and microbialites. A previously investigated, leeward fringing reef started to form contemporaneously (8·78 kyr bp ), but is thicker (up to 20 m) and solely prograded throughout the Holocene. A shallow Pocillopora assemblage and a deeper water Montipora assemblage were identified, but detrital facies dominate. At the Holocene reef base, only basalt was recovered. The Holocene windward–leeward differences are a consequence of less accommodation space on the eastern island side that eventually led to a more complex reef architecture. As a result of higher rates of exposure and flushing, the reef framework on the windward island side is more abundant and experienced stronger cementation. In the Pleistocene, the environmental conditions on the leeward island side were presumably unfavourable for fringing reef growth.